Fungal Community Structure of Macroalga Ulva Intestinalis Revealed by Miseq Sequencing - Agusman, Agusman; Danqing, Feng (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2017)
Since algae are well known as the host of fungi, the information about total fungal community associated with alga is needed to give the initial data that is useful for natural product discovery. The study on total fungal community associated with marine macroalga U. intestinalis from Xiamen-China was carried out using MiSeq, a powerful platform for microbial ecology studies. Metagenomics DNA was isolated from surfaces of the U. intestinalis thallus and rocks colonized by this alga andÂ  18S ribosomal RNA region was sequenced using MiSeq Illumina to yield 81360 sequences from 162720 reads, which average read length is 245.61 bp. The sequences were assigned to operational taxonomic units (OTUs), where 101 genera represent 5 phyla, 17 classes and 64 families of fungal. Ascomycota was the highest abundance share of fungal community at phylum level. Meanwhile Aspergillus, Blastobotrys, Alternaria, Knufia, and Fusarium were some of dominant genera found associated with U. intestinalis which have been reported as the promising source of natural products. By using MiSeq platform, this study revealed the total community structure of algicolous fungi associated with U. intestinalis.